The Importance of Halal Certified Products in Samarinda City: in the light of Maqasid Al-Syari'ah - Hasan, Maisyarah Rahmi (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2019)
Halal certification is a guarantee of safety for Muslims to be able to consume a product as evidenced by the inclusion of the halal logo on the product packaging. To realize the